2006
DOI: 10.1681/asn.2005070693
|View full text |Cite
|
Sign up to set email alerts
|

Src Activation of NF-κB Augments IL-1β–Induced Nitric Oxide Production in Mesangial Cells

Abstract: NF-B is a critical transcription factor that is involved in glomerulonephritis and inflammatory host responses and a critical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…This may indicate c-Src regulation of the glomerular function and renal microvasculature. An overexpression of c-Src in murine mesangial cells has been demonstrated to augment NF- κ B activation and nitric oxide production [22]. Furthermore, c-Src activation by in vitro blood-perfused juxtamedullary nephron technique contributed to afferent arteriole constriction induced by angiotensin II [23].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate c-Src regulation of the glomerular function and renal microvasculature. An overexpression of c-Src in murine mesangial cells has been demonstrated to augment NF- κ B activation and nitric oxide production [22]. Furthermore, c-Src activation by in vitro blood-perfused juxtamedullary nephron technique contributed to afferent arteriole constriction induced by angiotensin II [23].…”
Section: Discussionmentioning
confidence: 99%
“…Src and Syk kinases in innate cells either initiate or regulate various signaling pathways responding to many stimuli [9]. Activation of Src kinases mediate phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/IκBα/NF-κB signaling, and Src kinase plays an essential role to recruit or activate of immune cells [9,24,30,31,32]. The Src family of kinase inhibitors has been considered as anti-inflammatory reagents, for example, dasatinib is used for treatment of chronic myeloid leukemia [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, Choudhury et al showed that c-Src can signal to the nucleus to activate CDK2 and then promotes DNA synthesis in mesangial cells in response to platelet-derived growth factor (11). In addition, Jalal and Kone reported that Src mediates activation of NF-B, a critical transcription factor that is involved in GN and inflammatory host responses in mesangial cells (33). Because mesangial cell proliferation is the defining mechanism in mesangial proliferative GN, these results suggest that c-Src is critically involved in the pathogenesis of this disease.…”
Section: Role Of Src Kinase In Glomerulonephritismentioning
confidence: 99%